Effect of Children's Services In GKJW Church Growth Wiyung - Kasiatin Widianto; Lilis Setyarini; Meniati Hia (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
This is to examine the effect of child service on church growth at the Jawi Wetan Christian Church (GKJW) Wiyung Surabaya. This type of research is to explain the influence of child services on the growth of Jawi Wetan Wiyung Christian Church in Surabaya. Respondents who were the sample of this study were 50 people who were members of the Jawi Wetan Wiyung Christian Church congregation in Surabaya. In this study using data analysis techniques, namely methods that relate to the data in the sample, using descriptive statistics that is collecting, summarizing and presenting data systematically based on the sample analyzed with the aim to determine the relationship between a veriabel with other variables namely veriabel X ( independent) and the variable Y (dependent) with the analysis technique is the Pearson correlation technique. From the results of the data analysis test that has been obtained shows that the variable X has an influence with the Y variable which can be seen from the existing value where R Square = 0.595. This means that the influence of children's services on the growth of the GKJW Wiyung Surabaya church has a very influential relationship. With the correlation value R obtained at 0.696 with the influence on Y or R Square (coefficient of determination) = 0.484. This shows that the percentage contributing to the influence of X on Y. R Square = 0.484 implies that 48.4% of the contribution of X to Y. R Square ranges from 0 to 1. Note that the smaller the number of R Square, the weaker relationship X to Y. Because the data above the value of R Square is greater then it indicates that the stronger or increasing the relation of X to Y. So this can be said that the correlation value or the influence of the relationship on X and Y is good.